2016
DOI: 10.1083/jcb.201603081
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular TRPA1 mediates Ca2+ release from lysosomes in dorsal root ganglion neurons

Abstract: The temperature-sensitive TRP channel, TRPA1, is known to mediate Na+ and Ca2+ influx at the plasma membrane of sensory neurons. In this study, the authors show that TRPA1 is also present on the lysosomal membrane and mediates lysosome Ca2+ release in dorsal root ganglion neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
59
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(65 citation statements)
references
References 54 publications
3
59
0
Order By: Relevance
“…The problem of contamination can be minimized by raising the EGTA concentration, for example from 1 to 10 mM, which reduces the relative error from 12% to 1% in case of an assumed 10 µM calcium contamination (Patton et al, 2004). Shang et al (2016) used glycylphenylalanine 2-naphtylamide (GPN) to osmotically disrupt the lysosomes, which caused a small cytosolic calcium transient (Fig. 3 C in Shang et al [2016]; and our Fig.…”
Section: Introductionmentioning
confidence: 98%
“…The problem of contamination can be minimized by raising the EGTA concentration, for example from 1 to 10 mM, which reduces the relative error from 12% to 1% in case of an assumed 10 µM calcium contamination (Patton et al, 2004). Shang et al (2016) used glycylphenylalanine 2-naphtylamide (GPN) to osmotically disrupt the lysosomes, which caused a small cytosolic calcium transient (Fig. 3 C in Shang et al [2016]; and our Fig.…”
Section: Introductionmentioning
confidence: 98%
“…A recent study from Zhuan Zhou's group at Peking University discovered that TRPA1, a known Ca 2+ channel on plasma membranes, also acts on the lysosomal membrane to release Ca 2+ in mouse DRG (dorsal root ganglion) neurons . TRPA1‐mediated lysosomal Ca 2+ release contributes to approximately 40% of the overall [Ca 2+ ] i rise and directly triggers vesicle exocytosis and neuropeptide release, thereby contributing significantly to TRPA1‐related pain sensation . Future studies are needed to understand the mechanisms of lysosomal TRPA1 activation and whether it functions coordinately with plasma membranous TRPA1.…”
Section: Lysosomes In Secretionmentioning
confidence: 99%
“…Recently, Shang et al, reported the functional expression of TRPA1 in the peripheral lysosomes of dorsal root ganglion (DRG) neurons (Shang et al, 2016). Ca 2+ imaging studies has shown before that allyl isothiocyanate (AITC) could induce a TRPA1-dependent intracellular Ca 2+ release (Bandell et al, 2004; Jordt et al, 2004).…”
Section: Lysosomal Calcium Homeostasismentioning
confidence: 99%